Indium 111 autologous leucocyte scanning in lobar pneumonia and lung abscesses. Issue 12 (December 1985) - Saverymuttu, S H; Phillips, G; Peters, A M; Lavender, J P
Abstract : Indium 111 leucocyte scanning was used to examine the kinetics of granulocyte localisation in five patients with lobar pneumonia and four patients with lung abscess. Lung abscesses showed dense accumulation of labelled granulocytes within four hours of injection. In contrast, in all cases of lobar pneumonia granulocytes failed to accumulate over a period of up to 24 hours despite evidence of adequate perfusion and of uptake in inflammation elsewhere. These results suggest that the recruitment of granulocytes to lobar pneumonia may be terminated early in its clinical course.